Multilevel Governance and Indonesia’s Strategy for Climate Change Mitigation and Adaptation - Muhammad, Ali; Rizky, Lucitania; Sahide, Ahmad; Candra, Ilham Agustian; Prasetyo, Satria Iman (Universitas Muhammadiyah Yogyakarta, 2025)
This article critically examined Indonesia’s policies to mitigate and adapt to climate change within the global climate regime and local political dynamics. A qualitative method and a multilevel governance approach were utilized, emphasizing the dispersion of power both vertically among various levels of governance and horizontally among different quasi-governmental and non-governmental organizations and actors. The analysis unveiled that Indonesia’s climate change policies have involved supranational governance facilitated by global-level regimes and institutions. The government has played a strategic role in aligning itself with these global environmental regimes by implementing laws and policy measures to limit greenhouse gas emissions, control deforestation rates, and address forest degradation. Achieving these governance tasks involved active participation from local governments, municipalities, and non-state actors such as businesses and the community.